al-Insan al-Kamil Inda Badiuzzaman Said Nursi - Achmad Reza Hutama Al Faruqi (Universitas Darussalam Gontor, 2019)
This works tries to reveal the concept of the Perfect Man According to Badiuzzaman Said Nursi and how the methods used to achieve it, so it can reach the perfection and happiness of the world and the hereafter. In this study, Bediuzzaman stated that in fact Man was the best of Allah's creation, as this proved the testimony of the facts presented in Islam to mankind especially with humans and objects. Control of all tenderness and kindness to the intended destination is worship to God. So, the heart is tasked with controlling and controlling as well as the leader in which every tenderness and kindness comes from him and the view of reality is with a special way of worship with its gentleness. All of that is to walk like an army on the battlefield, as exemplified by Sahaba Rasulullah, and then increase the most perfect degree, the Prophet Muhammad. To equip man in a noble degree is to fulfil his obligations, namely noble morals, by worshiping Allah and avoiding His prohibitions. And humans if they have reached perfection, it will come to happiness that can be taken by means of faith in Allah SWT. and hereafter.